Cold plasma-mediated pesticide residue reduction and quality attribute modulation in cinnamon revealed by volatilomics and untargeted metabolomics - Siyao Liu; Danni Yang; Li Zhang; Xingping Zheng; Lilang Li; Yu Wang; Chenguang Zhou; Xiaobo Zou (Food Research International, 2026)

Deoxynivalenol impairs intestinal epithelial proliferation by disrupting the DEK-RPS6KB1 complex to suppress Wnt/β-catenin signaling - Lingjie Zeng; Ruqin Lin; Zhitian Yang; Danni Yu; Jintao Xu; Ziwan Qu; Zhikai Wu; Peiqiang Mu; Jun Jiang; Dongsheng Yao; Jikai Wen; Yiqun Deng (Journal of Environmental Sciences, 2026)

TRIF signaling is essential for the activation of dendritic cells during porcine rotavirus infection - Yu Sun; Tianming Niu; Ran Zhang; Danni Li; Mingyang Cheng; Chenxi Jiang; Yiran Shao; Hongyuan Wang; Ziqun Guo; Wentao Yang; Xin Cao; Chunfeng Wang; et al. (Veterinary Microbiology, 2026)

Cyanobacterial extracellular polymeric substances empowered biological aqua crust formation via selective mineral adsorption for sustainable metal(loid) bioremediation - Yuanyuan Jiang; Guobao Wang; Zekai Feng; Daijie Chen; Chiyu Chen; Hang Yu; Danni Liu; Zhicheng Liu; Jean Louis Morel; Yuanqing Chao; Yetao Tang; Rongliang Qiu; et al. (Journal of Hazardous Materials, 2026)

Host-microbial co-regulation mediates rumen volatile fatty acid production and utilization in dairy cows - Wei Wang; Jianrong Ren; Jing Li; Danni Li; Zhenyu Wei; Xinmei Li; Huimei Fan; Yuejuan Zhang; Jingyi Xu; Guanghao Xu; Yu Jiang; Junhu Yao; et al. (Science China Life Sciences, 2026)

Transforming from ‘natural tools’ into ‘custom sensors’: combining directionally designed biological nanopore electrochemistry sensing lumens with AI-driven analytics to pioneer a new paradigm for food analysis - Yanyang Yu; Yongfei Deng; Zhiyong Cui; Yueming Wang; Chenxi Zhang; Jinna Wang; Danni Zhang; Tianxing Zhou; Chuyue Gong; Shengli Zhang (Trends in Food Science & Technology, 2026)

Lactiplantibacillus plantarum enables metal recovery from spent LiNi0.33Co0.33Mn0.33O2 cathode via EPS-mediated synergistic bioleaching - Min Li; Hong Wang; Danni Zhang; Zhong Li; Qiuli Xia; Xianjun Guan; Yaojie Yu; Linlin Tong; Junting Tong; Yongqiang Fan; Fuhui Wang; Dake Xu (Journal of Hazardous Materials, 2026)

Synergistic lattice strain and vacancy engineering in Cd Sb pyrochlore oxides for efficient CO2 electroreduction to CO - Yujie Wang; Jiaying Li; Zihan Gao; Tianbo Jia; Ning Yu; Xiang Cui; Danni Xun; Umirzakov Batokhodja; Chunyang Zhai; Shuying Gao; Hengcong Tao (Chemical Engineering Journal, 2026)

Mechanism of PP2A affecting ubiquitination pathway in spermatogenesis - Huamei Ju; Ziliang Geng; Binyan Chen; Yuwei Shang; Xia Chen; Danni Wang; Wenbin Wang; Huiting Sun; Yichao Shi; Jiajun Yu (Reproductive Biology, 2026)

Identification of key taste active compounds and potential umami peptides in soft-boiled chicken based on taste recombination and virtual screening - Shui Jiang; Xiangyuan Li; Lexin Zhao; Shuang Bai; Danni Zhang; Hengli Meng; Zhiyong Cui; Xiaoming Wang; Bo Yu; Yuan Liu (Food Chemistry, 2026)

Natural compounds as potential anticancer agents aimed at ovarian cancer stem cells - Yu-Fei Zhu; Danni Ding; Yang Yu; Fang-Yuan Liu; Feng-Juan Han (Phytochemistry Reviews, 2026)

Interplay between manganese and algal metabolism: From metabolic regulation to photochemical feedbacks via algal organic matter - Danni Cui; Yuan Gui; Ziwei Guo; Huan He; Xi Deng; Xi-Zhi Niu; Yu Luo; Bin Huang; Xuejun Pan (Journal of Hazardous Materials, 2026)

Effects of simulated nitrogen deposition on N fate in a temperate steppe: Evidence from multi-year 15N isotope study - Zhilu Sheng; Yongmei Huang; Lei Duan; Kejian He; Danni Xie; Narigele Borjigin; Hanyue Yang; Yu Qi; Engui Li (Journal of Environmental Management, 2025)

Effect of honey-aloe paste on alleviating loperamide-induced constipation, in relation to regulation on gastrointestinal function and intestinal microenvironment - Danni Chang; Fanhua Wu; Yu Yang; Jinjin Zhang; Tianchen Ma; Sen Guo; Haoan Zhao; Wei Cao (Food Research International, 2025)

Switching from flood to drip irrigation changes soil labile organic carbon in arid agricultural fields - Danni Wang; Fangfang Qin; Shiying Lin; Yan Wu; Yongxiang Yu; Yaying Li; Huaiying Yao (Environmental Research, 2025)

Limosilactobacillus reuteri FN041 alleviates cow's milk β-lactoglobulin–induced food allergy through immune modulation and gut microbiota remodeling - Renqiang Yu; Weijia Li; Zhou Zhou; Yue Yin; Zichen Luo; Ce Qi; Shanyu Jiang; Xiaoqing Chen; Danni Ye; Jin Sun (Food Bioscience, 2025)

Intestinal barrier disruption by cadmium and microplastics: Mechanistic insights from integrated metabolomic and proteomic analysis in mice - Jiajie Yang; Danni Wang; Junyu Huang; Ting Zhao; Maoting Chen; Shengxuan Lin; Xinqi Yu; Falong Yang; Haifeng Liu; Shiwen Xu; Dechun Chen (Environmental Pollution, 2025)

True‑Triaxial Experimental Study on Failure Process and Acoustic Emission Characteristics of Intermittent Rockbursts - Danni Luo; Yahui Zhang; Yu Hu; Guanyan Chen; Guoshao Su (Rock Mechanics and Rock Engineering, 2025)

Molecular biomarkers for the prognosis of breast cancer: role of amino acid metabolism genes - Yudong Zhou; Shibo Yu; Lizhe Zhu; Yalong Wang; Chenglong Duan; Danni Li; Jinsui Du; Jiaqi Zhang; Jianing Zhang; Ruichao Ma; Jianjun He; Yu Ren; et al. (Journal of Physiology and Biochemistry, 2025)
The development of precise molecular biomarkers for breast cancer prognosis holds immense potential to improve treatment outcomes. This study aimed to investigate the role of amino acid metabolism genes as predictive markers for breast cancer prognosis and their association with the immune-tumour microenvironment. By employing advanced machine learning algorithms and bioinformatics analysis techniques, the impact of amino acid metabolism-related genes (AAMRGs) on the immune status and overall survival of patients with breast cancer was examined. An AAMRG-based risk model was established to assess the prognostic significance. Validated risk models (AIMP2, IYD, and QARS1) accurately predicted patient outcomes [1 y: 0.87 (0.96–0.78); 3 y: 0.82 (0.87–0.76); 5 y: 0.80 (0.86–0.75)]. Furthermore, this study revealed evidence suggesting that QARS1 may influence breast cancer cell proliferation through methionine metabolism. This analysis provides valuable insights into the mechanisms of breast cancer, emphasizing the significance of AAMRGs as prognostic biomarkers and potential therapeutic targets for optimizing personalized treatment strategies.

Strengthened double-diffusive convection induced by the combined effect of tropical cyclones and a mesoscale eddy - Yanwei Zhang; Weihan Ruan; Danni Lyu; Jiancheng Yu (Progress in Oceanography, 2025)

Developing a Ni-grafted magnetic nanoparticle for direct CotA capture in rapid detoxification of aflatoxin B1 - Chengyu Zhang; Danni Wang; Cong Wang; Huijuan Yu; Peng Zhong; Weifan Dang; Yufan Yang; Yuefei Wang; Xiaohui Yan (Journal of Hazardous Materials, 2025)

Nanozyme and bifunctional nanobody-based colorimetric-SERS dual-mode Immunosensor for microcystin-LR detection - Long Wu; Luyao Jiao; Danni Xue; Yueqing Li; Yu Han; Wei Ouyang; Qi Chen (Food Chemistry, 2025)

Degrading poly(lactic acid) microplastic induces priming in agricultural soils - Yan Wu; Zihuan Wang; Yongxiang Yu; Xinhui Liu; Danni Wang; Juan Wang; Yaying Li; Biao Zhu; Joann K. Whalen; Huaiying Yao (Applied Soil Ecology, 2025)

Comprehensive lipidomic profiling of human milk from lactating women across varying lactation stages and gestational ages - Min Zhao; Zhenying Chen; Danni Ye; Renqiang Yu; Qin Yang (Food Chemistry, 2025)

Human milk-derived Limosilactobacillus reuteri FN041 ameliorates DSS-induced colitis by remodeling gut microbiota and metabolites in mice - Zichen Luo; Jin Sun; Ji Liu; Ping Yu; Danni Ye; Ce Qi; Xiaoqing Chen; Renqiang Yu (Food Bioscience, 2025)

A ratiometric fluorescent biosensor based on catalytic hairpin assembly reaction for ultrasensitive detection of aflatoxin-producing genes - Tao Yu; Xin Chen; Danni Sun; Dezhao Kong; Zhirong Wang; Feng Lin; Yaqi Li (Food Bioscience, 2024)

Modeling of extreme waves in the South China Sea under the influence of tropical cyclones: long-term statistical perspective in Xisha reef islands - Yu Yao; Danni Zhong; Jiangxia Li; Erman Peng; Conghao Xu; Long Chen; Ze Sun (Natural Hazards, 2024)

Advancements and challenges on SERS-based multimodal biosensors for biotoxin detection - Xuemei Tang; Huan Jiang; Ruiming Wen; Danni Xue; Wei Zeng; Yu Han; Long Wu (Trends in Food Science & Technology, 2024)

Mineralization and microbial utilization of poly(lactic acid) microplastic in soil - Yongxiang Yu; Shiying Lin; Binoy Sarkar; Juan Wang; Xinhui Liu; Danni Wang; Tida Ge; Yaying Li; Biao Zhu; Huaiying Yao (Journal of Hazardous Materials, 2024)

Self-heating photothermal synergistic catalytic decomposition of carcinogenic formaldehyde by α-MnO2 at ambient temperature: Functional roles of surface acidic-basic sites - Danni Ding; Zeyi Cheng; Yu Zhou; Nan Zhang; Wang Ran; Shaopeng Rong (Journal of Environmental Chemical Engineering, 2024)

Comparative Transcriptome Analysis Reveals the Complex Molecular Mechanisms Underlying Ultraviolet-B Tolerance in Brassica rapa var. rapa - Yu Zhang; Jiancan Du; Tingting Ni; Danni Yang; Chongde Wang; Yunqiang Yang; Yuanwen Duan; Yongping Yang; Xudong Sun (Journal of Plant Growth Regulation, 2024)

A strategy to assess the use-phase carbon footprint from energy losses in electric vehicle battery - Boran Yang; Chenran Du; Hang Zhang; Xiaoli Ma; Xueling Shen; Dong Wang; Zhanglong Yu; Qian Huang; Danni Gao; Yanping Yin; Yanyan Fang; Ran Xu (Journal of Cleaner Production, 2024)

Bandgap engineering of carbon nitride by formic acid assisted thermal treatment for photocatalytic degradation of tetracycline hydrochloride - Yu Zhou; Danni Jiang; Zhiwei Wang; Lidong Yi; Jiaxin Sun; Dingli Liu; Xiaoxue Yu; Yonghua Chen (Chemical Engineering Journal, 2024)

The response of needle stoichiometry to 10-year N addition and 4-year cessation of N addition in a subtropical Masson pine plantation of China - Dongxing Yang; Jiawei Zhang; Qian Yu; Danni Xie; Ronghua Kang; Ting Zhang; Gaoyue Si; Jan Mulder; Yongmei Huang; Lei Duan (Plant and Soil, 2024)

Investigation into the degradation patterns of the physical and mechanical characteristics of phyllite within a hydrothermal environment - Jiangbo Xu; Xianglong Zeng; Haohui Sun; Wei Qiao; Xiong Wu; Danni Zhao; Yu Qi (Bulletin of Engineering Geology and the Environment, 2024)

Guest adaptative supramolecular sensing strategy for warning the risky aflatoxins in contaminated cereals - Danni Wang; Wenhui Li; Wenqian Cheng; Yi Wang; Zhe Zheng; Xin-Yue Hu; Huan-Yu Wang; Xiaoyu Zhang; Huijuan Yu; Dong-Sheng Guo; Yuefei Wang (Journal of Hazardous Materials, 2024)

A numerical investigation of the 2DH wave characteristics across a fringing reef profile with reef-flat excavation pit - Yu Yao; Danni Zhong; Qijia Shi; Ji Wu; Jiangxia Li (Ocean Engineering, 2024)

Persistence and potential risks of tetracyclines and their transformation products in two typical different animal manure composting treatments - Danni Wu; Shiting Dai; Haodi Feng; S.H.P. Parakrama Karunaratne; Min Yang; Yu Zhang (Environmental Pollution, 2024)

Surface acidic sites strengthened core-shell HC@MnO2 for enhanced gaseous ammonia adsorption - Weijiang He; Jingling Lu; Nan Zhang; Yu Zhou; Danni Ding; Yanfang Feng; Shaopeng Rong (Chemosphere, 2023)

Stabilization of calcium arsenic residues via the formation of ferrous/ferric arsenate - Yumeng Wang; Jiaxi Zhang; Shaofeng Wang; Xiangfeng Zeng; Xin Wang; Peiwen Zhang; Yu Song; Danni Zhang; Yongfeng Jia (Chemical Engineering Journal, 2023)

Enabling financial development: linking innovation and CO2 emissions through equity and credit financing - Danni Yu; Badar Latif (Environmental Science and Pollution Research, 2023)

Construction of α-MnO2/g-C3N4 Z-scheme heterojunction for photothermal synergistic catalytic decomposition of formaldehyde - Nan Zhang; Weijiang He; Zeyi Cheng; Jingling Lu; Yu Zhou; Danni Ding; Shaopeng Rong (Chemical Engineering Journal, 2023)

Enhancement of acidic sites in layered MnO2 for the highly efficient selective catalytic oxidation of gaseous ammonia - Yu Zhou; Shaopeng Rong; Huifang Xie; Yanfang Feng; Danni Ding; Weijiang He; Nan Zhang; Jingling Lu (Journal of Environmental Chemical Engineering, 2023)

Comparative Transcriptome and Hormone Analysis of Mature Leaves and New Shoots in Tea Cuttings (Camellia sinensis) among Three Cultivars with Different Rooting Abilities - Kai Fan; Yujie Shi; Danni Luo; Wenjun Qian; Jiazhi Shen; Shibo Ding; Zhaotang Ding; Yu Wang (Journal of Plant Growth Regulation, 2022)

Extracellular vesicles derived from human bone marrow mesenchymal stem cells protect rats against acute myocardial infarction-induced heart failure - Liying Xuan; Danni Fu; Dong Zhen; Chengxi Wei; Dongsong Bai; Lijun Yu; Guohua Gong (Cell and Tissue Research, 2022)

Oxidative degradation of p-chlorophenol by the persulfate-doped Fe–Mn bimetallic hydroxide, the parametrical significance, and systematical optimization - Tao Huang; Jing Du; Danni Yu; Shihan Deng; Shuwen Zhang; Longfei Liu (Environmental Science and Pollution Research, 2022)

Competition for electrons between pyridine and quinoline during their simultaneous biodegradation - Hua Xu; Weihua Sun; Ning Yan; Danni Li; Xueqi Wang; Tingting Yu; Yongming Zhang; Bruce E. Rittmann (Environmental Science and Pollution Research, 2017)

Identification of nucleolus-localized PTEN and its function in regulating ribosome biogenesis - Pingdong Li; Danni Wang; Haiyang Li; Zhenkun Yu; Xiaohong Chen; Jugao Fang (Molecular Biology Reports, 2014)